Are kinesins required for organelle trafficking in plant cells? - Giampiero eCai; Mauro eCresti (Frontiers in Plant Science, 2012)
Plant cells exhibit active movement of membrane-bounded materials, which is more pronounced in large cells but is also appreciable in medium-sized cells and in tip-growing cells (such as pollen tubes and root hairs). Trafficking of organelles (such as Golgi bodies, endoplasmic reticulum, peroxisomes, and mitochondria) and vesicles is essential for plant cell physiology and allows a more or less homogeneous distribution of the cell content. It is well established that the long-range trafficking of organelles is dependent essentially on the network of actin filaments and is powered by the enzyme activity of myosins. However, some lines of evidence suggest that microtubules and members of the kinesin microtubule-based motor superfamily might have a role in the positioning and/or short-range movement of cell organelles and vesicles. Data collected in different cells (such as trichomes and pollen tubes), in specific stages of the plant cell life cycle (for example during phragmoplast development) and for different organelle classes (mitochondria, Golgi bodies and chloroplasts) encourage the hypothesis that microtubule-based motors might play subtle yet unclarified roles in organelle trafficking. In some cases, this function could be carried out in cooperation with actin filaments according to the model of functional cooperation by which motors of different families are associated with the organelle surface. Since available data did not provide an unambiguous conclusion with regard to the role of kinesins in organelle transport, here we want to debate such hypothesis.